[Ethnographic Study of Gay Men in Australia and New Zealand] - Appleby, George A. (1998)
Keywords: dept.swk; faculty_collection; sabbatical_report

Impact of Welfare Reform in Connecticut. - Rofuth, Todd (Fall;Social Work., 1998)
Keywords: dept.swk; faculty_collection; sabbatical_report

Empirical (qualitative) Research on Social Work Education. - Senzer, Mark (Spring;Social Work., 1998)
Keywords: dept.swk; faculty_collection; sabbatical_report

"Thoughts of a Social Work Distance Education Teacher." - Jennings, Joanne (1997)
Keywords: dept.swk; faculty_collection; sabbatical_report

MSW Student's Integration of Theory and Practice: A Guide for Educators and Students. - Michlin, P. (1995)
Keywords: dept.swk; faculty_collection; sabbatical_report

The Gender Dance in Couples Therapy - Worden, Mark; Worden, Barbara Drahus (Brooks/Cole, 1998)
Keywords: Marital psychotherapy; dept.swk; faculty_collection

Social Work Students' Perception of Connecting Theory and Practice - Parivash, Michlin Minou (Thesis D.S.W.--Yeshiva University., 1992)
Keywords: Connecticut; New Haven; Social work education; dept.swk; faculty_collection

Teaching Aids to Adults: A Resource for Acquired Immune Deficiency Syndrome Instruction - Appleby, George A.; Connecticut State Department of Education (State of Connecticut, Department of Education, 1989)
Keywords: AIDS (Disease); Study and teaching; dept.swk; faculty_collection

The Use of Mutual Aid by Russian-Jewish Immigrants in Two Connecticut Communities: An Analysis of an Informal Helping System - Siegel, Elbert (Thesis Ph.D.--Columbia University., 1988)
Keywords: Connecticut; History; History; Connecticut; Jews, Russian; dept.swk; faculty_collection

The Relationship of Program Change and Select Structural and Contextual Organizational Properties of Fifteen Mental Health Agencies - Appleby, George A. (Thesis D.S.W.--Columbia University., 1984)
Keywords: Administration; Mental health facilities; dept.swk; faculty_collection

Resources Handbook for S.W. 377: Intervention Methods/Skills II (the group) - Southern Connecticut State College Division of Social Work (Southern Connecticut State College, 1978)
Keywords: Handbooks, manuals, etc; Social work education; dept.swk; faculty_collection

Family violence - Hutchings, N. (Peace Review, 1992)
Keywords: dept.swk

Extending health care to afdc recipients who obtain jobs: Results of a demonstration - Rofuth, T.W.; Weiss, H. (Health and Social Work, 1991)
This study investigated the outcomes of a demonstration project that provided free medical coverage to former Aid to Families with Dependent Children (AFDC) recipients who were holding jobs with limited or no health benefits. Data were collected on the Medicaid expenditures of 54 eligible participants and their dependents for up to two years before they exited welfare; the expenditures averaged 56 percent less for adults and 45 percent less for children than the respective AFDC averages for the county. Because only 22 percent of the eligible participants took advantage of the program, telephone interviews also were conducted with 24 people who did not participate in or dropped out of the health plan. The main reasons cited for not enrolling were a misunderstanding of the program, a claim that no notification of the program was received, and a lack of interest. These results and their policy implications are presented in the context of the Family Support Act's mandate that states extend medical assistance coverage to AFDC recipients whose cases are closed because of employment. © 1991 by the National Association of Social Workers, Inc.
Keywords: Aid to Families with Dependent Children; Cost-Benefit Analysis; Employment; Female; Health Education; Health Expenditures; Human; Insurance, Health; Male; Maryland; Medicaid; United States; article; cost benefit analysis; dept.swk; economics; employment; female; health care cost; health education; health insurance; human; male; medicaid; organization and management; social security; standard; utilization review

Reducing interethnic social distance among adolescents through participation in life-skills groups - Howe, E. (International Journal of Adolescent Medicine and Health, 1999)
Keywords: adolescence; adolescent; article; attitude; cognitive defect; coping behavior; counseling; dept.swk; ethnic group; female; group psychology; human; human experiment; male; peer-reviewed; problem solving; social behavior; social interaction; social psychology; social status; socialization

Can applied science in environmental monitoring transform science education? - Holloway, S.; Rofuth, T.W.; Gruner, H.; Mimo, A. (Educational Forum, 1998)
Keywords: dept.swk

Onset, course, and outcome of schizophrenia. - Rakfeldt, Jaak; McGlashan, Thomas (Current Opinions in Psychiatry, 1996)
The studies reviewed here reflect many important aspects of the onset, course, and outcome of schizophrenia; that is, premorbid factors, childhood and late-life onset, the positive-negative syndrome dichotomy, co-occurring substance abuse, outcome research, and theoretical issues. Unsurprisingly, heterogeneity of course and outcome emerges as a major theme., (C) Lippincott-Raven Publishers.
Keywords: depression; dept.swk; disease course; human; onset age; schizophrenia; short survey; substance abuse

Setting goals and objectives for LD children. Process and problems - Gallistel, E.R. (Journal of Learning Disabilities, 1978)
Keywords: Adolescent; Child; Child, Preschool; Education, Special; Female; Goals; Human; Language Development; Learning Disorders; Male; Motor Skills; Social Behavior; United States; dept.sed; handicapped child; law; learning disorder; legal aspect; major clinical study; preschool child; school child; therapy

Differential approaches to prevalence estimates of learning disabilities - Minskoff, J Gerald (Annals of the New York Academy of Sciences, 1973)
Keywords: Attention Deficit Disorder with Hyperactivity; Child; Human; Learning Disorders; United States; article; attention deficit disorder; child; dept.sed; human; learning disorder

Empowerment through collaboration in a state university system - Brower, Irene; Nancy Coleman; Ivry, Patricia; Leipzig, Barbara; Nemzer, Beatrice; Nilsson, Andrew; Sosnowitz, Barbara (Journal of Teaching in Social Work, 1989)
Historically, social workers have been aware of the power of group resources and the importance of networking for their clients and for themselves as professionals. This article is the outgrowth of a collaboration paper presented by the authors at the Association of Baccalaureate Social Work Program Directors Annual Conference on September 22, 1986 in San Antonio, Texas. Four separate social work education programs within a state university system formed an informal collaborative association to address common concerns, develop strategies to enhance resources and to foster mutual support. The context, developmental process, barriers, activities, issues, outcomes and benefits of the collaborative association are described. © 1989 Taylor & Francis Group, LLC.
Keywords: dept.swk

Suicide attempts and alcoholism - Hesselbrock, M.; Hesselbrock, V.; Syzmanski, K.; Weidenman, M. (Journal of Studies on Alcohol, 1988)
This study examined the association among suicide attempts, parental alcoholism, psychopathology and drinking history in a sample of hospitalized alcoholics. Suicide attempters were found to have multiple psychiatric diagnoses (e.g., depression, antisocial personality disorder and substance abuse) and more severe psychiatric symptoms than nonattempters. Alcoholic suicide attempters also tended to have a parental history of alcoholism and began abusing alcohol at an early age. Alcohol abuse symptoms during the month before, and 6 month before, the current hospitalization were generally similar for suicide attempters and nonattempters. Clinical implications of the findings are discussed.
Keywords: adult; age; alcoholism; dept.swk; epidemiology; female; human; male; mental disease; normal human; oral drug administration; preliminary communication; psychological aspect; suicide attempt

Impact of a geriatric consultation team on discharge placement and repeat hospitalization - Saltz, Constance C; Mcvey, Laura J; Becker, Peter M; Feussner, John R; Cohen, Harvey J (Gerontologist, 1988)
Keywords: age; consultation; dept.swk; hospitalization; human; major clinical study

Effects of retesting with the beck and zung depression scales in alcoholics - Choquette, Keith A; Hesselbrock, Michie N (Alcohol and Alcoholism, 1987)
The present study assessed the presence of testing effects arising from the repeated administration of both the Beck and Zung depression scales to a group of 60 inpatient alcoholics. Thirty-seven men and 23 women were randomly assigned to one of three groups and administered the depression scales on one, two or three occasions, in successive weeks of treatment. Although the between group comparisons of initial test administration did not indicate a true change in depression, a within group comparison of initial with subsequent test administrations indicated a clear improvement in depression scores on both scales. Apparently the result of the reactive effects of testing, the within group differences could easily mislead a researcher into believing depression was alleviated when in fact it was not. This sizeable testing effect has obvious implications for studies which repeatedly assess depression. © 1987 Medical Council on Alcoholism.
Keywords: Adult; Aged; Aged, 80 and over; Alcoholism; Depressive Disorder; Emotions; Female; Hospitalization; Human; Male; Middle Age; Psychiatric Status Rating Scales; Support, U.S. Gov't, P.H.S.; Time Factors; adult; aged; alcoholism; article; clinical trial; depression; dept.swk; emotion; female; hospitalization; human; male; randomized controlled trial; rating scale; time; ⛔ No DOI found

Sources of strain between physicians and social workers: Implications for social workers in health care settings - Mizrahi, T.; Abramson, J. (Social Work in Health Care, 1985)
This paper analyzes the sources of strain between the professions of medicine and social work. The two professions are compared in relation to (1) the organization and socialization process of professional training; (2) perspectives on patient care, illness and role of the health care professional; (3) attitudes toward knowledge and data; (4) attitudes toward and preparation for teamwork; (5) perspectives on the role of the patient; (6) perceptions of social work’s function. © 1985 Taylor & Francis Group, LLC.
Keywords: Attitude of Health Personnel; Human; Internship and Residency; Interprofessional Relations; Medical Staff, Hospital; Patient Advocacy; Professional-Patient Relations; Role; Sick Role; Social Perception; Social Work; Socialization; dept.swk; human; organization and management; physician; psychological aspect; short survey; social aspect; social worker; training; united states

Parents' evaluations of genetic counselling. - Black, Rita Beck (Patient Counselling and Health Education, 1980)
Genetic counselling represents a new and important health service, but little is known about how the clients of genetic clinics actually experience and view the genetic counselling process. This paper reports on the evaluations made by clients of a genetics clinic and their recommendations for ways to improve and expand this service. In their comments, clients stressed the need for more time and individual attention from genetic counsellors, additional follow-up and supportive counselling, and increased efforts to educate the general public about birth defects. Their recommendations are discussed in terms of the implications for developing and improving genetic counselling services.
Keywords: anxiety; dept.swk; genetic counseling; heredity; medical education; medical examination; parent; prevention

Self-help for grandmothers parenting again - Winston, Carole A (Journal of Social Distress and The Homeless, 1999)
Increasingly, grandmothers are parenting grandchildren in homes where parental presence is sporadic or nonexistent. A disproportionate percentage of African American grandparents fall in this category. The author reviews the literature on the African American grandmother in the context of the African American family and describes a practice model for service provision to those women who seek support as they “parent again.”
Keywords: African American; Empowerment model; Parenting grandparents; Support group; dept.swk

Alcohol Use Among Latino Males - Colon, Edgar (Alcoholism Treatment Quarterly, 1998)
This paper examines the factors surrounding the use of alcohol among Latino males. Prevention and treatment strategies for the provision of culturally competent treatment services are proposed, based on an analysis of the literature.
Keywords: alcoholism; article; dept.swk; ethnic group; health care delivery; health care planning; human; incidence; preventive health service; united states

Distance learning in social work education - Siegel, Elbert; Jennings, Joanne G; Conklin, Jack; Flynn, Shelly A Napoletano (Journal of Social Work Education, 1998)
This article reports data collected from a national survey of all accredited social work programs conducted between December 1995 and February 1996. The purpose was to assess current usage of distance learning in social work education. The findings suggest that the use of distance learning has increased, and that the most prevalent issues reported by educators involve adapting instructional material for course presentation and faculty preparation. Implications of the study findings for social work education are also discussed.
Keywords: dept.swk

Normalizing acute care: A day hospital/crisis residence alternative to inpatient hospitalization - Rakfeldt, J.; Tebes, J.K.; Steiner, J.; Walker, P.L.; Davidson, L.; Sledge, W.H. (Journal of Nervous and Mental Disease, 1997)
Normalization is the use of culturally valued means to enable people with disabilities to live culturally valued lives. In this article, the authors describe an effort to bring normalization practices to acute psychiatric care. They describe a day hospital/crisis respite diversion program that serves as an alternative to acute inpatient hospitalization and sketch the research project that fostered it. The authors argue that a day hospital/crisis respite provides effective clinical care comparable to inpatient hospitalization but achieves greater potential for recovery through a normalizing philosophy and practice. An implication of this finding is that such programs based on the principle of normalization may be both cost effective as well as more empowering for patients.
Keywords: Acute Disease; Adult; Bipolar Disorder; Community Mental Health Centers; Cost-Benefit Analysis; Crisis Intervention; Day Care; Female; Group Homes; Health Care Costs; Health Services Research; Hospitalization; Humans; Mental Disorders; Psychotic Disorders; adult; article; case report; crisis intervention; day hospital; dept.swk; female; human

Program design and planning strategies in the delivery of culturally competent health and mental health prevention and treatment services to latino communities - Colon, Edgar (Journal of Multicultural Social Work, 1997)
It is important that the delivery of health and mental health prevention and treatment services within Latino communities be culturally sensitive. This article outlines several ways in which agencies can develop programs that can meet the needs of Latino communities. The most important aspect of the provision of health prevention and treatment services is that the organization integrates itself into the community through outreach, recruitment, and inclusion in decision-making. In addition, the organization needs to be structured so communication and participation from the community and health professionals are open and mixed. Otherwise, the likelihood of success of the provision of services in the community will be diminished. © 1996 Taylor & Francis Group, LLC.
Keywords: dept.swk

Working memory, attention, and communication disturbances in schizophrenia. - Docherty, Nancy M; Hawkins, Keith A; Hoffman, Ralph E; Quinlan, Donald M; Rakfeldt, Jaak; Sledge, William H (Journal of Abnormal Psychology, 1996)
The authors hypothesized that schizophrenic communication disturbances reflect specific cognitive deficits in the areas of working memory and attention. They examined the cognitive correlates of communication disturbances, as measured by linguistic reference performance, in schizophrenic (n = 48), bipolar (n = 24), and nonpsychiatric control (n = 23) individuals. Reference performance ratings in the schizophrenic patients were associated with scores on tests of working memory and attention and were not related to performance on concept formation or verbal fluency tests. In contrast, in the bipolar and nonpsychiatric individuals, reference performance was associated with concept formation and verbal fluency test scores but was not related to performance on tests of working memory. Implications with respect to the processes underlying schizophrenic communication disturbances are discussed.
Keywords: adult; article; attention; bipolar depression; cognitive defect; controlled study; dept.swk; female; human; interpersonal communication; major clinical study; male; memory; rating scale; schizophrenia; task performance; verbal communication

Persistence by 2-Year college graduates to 4-Year colleges and universities. - Dworkin, Stephen L (Community College Journal of Research and Practice, 1996)
Most community college graduates do not continue on for study in 4-year colleges and universities. Fewer than 20% do so within the first few years after receiving their associate's degrees. Concerns have been expressed about the extent to which older students (e.g., students who received their degrees at age 25 and above) persist (go on) to 4-year colleges and universities and about the correlates of persistence for this group. The purpose of this study was to examine the relationships between a selected number of academic, social, and personal variables in the context of predicting persistence to a 4-year public university among older graduates of a New England state’s public 2-year institutions. Data were collected in 1988 and 1989 from a random sample of 3,762 older associate's degree students from the 12 community colleges in Connecticut. These data were then subjected to a two-group, single-function discriminant function analysis to determine the predictive power of the dependent measures used in the study. The results indicated that the higher the perceptions of social and institutional support in community colleges and the higher the age of the graduates, the more apt they were to persist to a 4-year institution. Further analysis, however, revealed that the average persister was 38 years old, whereas the average attritor was 34 years old, suggesting the need for further research among 2-year college populations among the over-30 age group as well as replication of the study in states with both similar and dissimilar demographic shifts in college populations. © 1996 Taylor and Francis Group, LLC.
Keywords: dept.swk

Chapter 1: AIDS and Homophobia/Heterosexism - Appleby, George Alan (Journal of Gay and Lesbian Social Services, 1995)
Homophobia and heterosexism are complementary social processes that shaped the social construction and the public health response to AIDS. Both concepts view gay and lesbian oppression from different vantage points. Homophobia is a weapon of sexism and is manifested in fear and hatred. Heterosexism is an ideological system that denigrates non-heterosexual behavior. Both processes are well served by the social institutions of family, religion, law, and the ideologies of sexuality and gender. The consequences have been societal and personal: inadequate HIV medical and social services; lack of a national AIDS policy; widespread discrimination and prejudice against gay men, lesbians, and persons living with AIDS; stress, violence, and suicide; substance abuse; and HIV risk behavior and relapse. Mental health and social services, social supports, education and prevention programs, community development, and social action to broaden civil rights and to challenge institutional oppression are required to counter the ravages of hate and discrimination. © 1995 Taylor & Francis Group, LLC.
Keywords: dept.swk

Training gerontological social workers for nursing home practice - Gesino, Jack Paul; Siegel, Elbert (Gerontology & Geriatrics Education, 1995)
An escalating elderly population has necessitated a corresponding need for social workers trained in gerontology and who can practice in nursing homes. In order to enhance professional knowledge and skills, the authors present a teaching model that uses an apprenticeship framework to help students develop social work skills in working with elderly residents in long term care facilities. Responses to student reaction worksheets were analyzed in order to assess student experiences, the progress of skill development and the amelioration of bias as a relationship develops develops between client and social worker. The authors propose the use of a "reflective practicum" enhanced by group processes as a way to enhance training. © 1995 Taylor & Francis Group, LLC.
Keywords: dept.swk

No place like home: A study of two homeless shelters - Friedman, Bruce David (Journal of Social Distress and The Homeless, 1994)
Homelessness is one of the most pressing social problems today. Society has responded to the problem with the creation of homeless shelters. Yet, the nature of the operation of the shelter is not defined. This study explored the operations of two single adult homeless shelters to understand how they operate in addressing the problem of homelessness. The study identified two different types of services, one called `'house” and the other `'home”. House services provided basic food, shelter, and linkage to social services, which fulfilled the basic definition of the problem of homelessness as defined by the Institute of Medicine. Home services provided the basic services of house but also went one step beyond by providing these services within the context of a supportive environment, thus creating informal social supports. The study discusses the implications of each of these modalities in addressing the problems associated with people who are homeless as well as the differences in policies and structures which contribute to one shelter providing house and the other home services.
Keywords: dept.swk